Pengujian Validitas dan Reliabilitas Instrumen Manajemen Diri Remaja: Rasch Model Analysis - Salsabila, Fadiya; Nurihsan, Juntika; Sunarya, Yaya (Jurnal Bimbingan dan Konseling Terapan, 2023)
This study aims to analyze the validity and reliability of self-management instruments using the Rasch Model. The Rasch Model method has the advantage of being able to provide more accurate estimates and being able to find model inaccuracies. The research was conducted using quantitative methods with a survey research design. The subjects in this study were 100 high school students. Data analysis was performed using the Rasch Model method with the Winstep application version 3.73. The results of the study showed that the Cronbach alpha value obtained was 0.73 which was included in the good category. Meanwhile, the personal reliability score of 0.76 is a good category and the item reliability score of 0.96 is a special category. Therefore, self-management instruments can be used by counseling teachers to see the condition of students' self-management and can develop counseling services that suit students' needs based on the results of self-management assessments.